Nilai-Nilai Religius dalam Film Animasi Nussa dan Rara sebagai Alternatif Media Pembelajaran Sastra di SD - Dewi Maryanti Dewi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The problem with this research is the lack of application of religious values ​​among elementary school children. Purpose of this study is to describe religious values in the animated film Nussa and Rara as an alternative learning media in elementary schools. Method used in this research is content analysis. Data collection techniques were carried out by observation and documentation. This study uses the theory of Glock and Strak in analyzing the religious values contained in the animated film Nussa and Rara. The findings of this study contained five aspects in the animated film Nussa and Rara, namely aspects of belief in the existence of God, aspects of worship practices by praying and making sacrifices, aspects of experience and appreciation by feeling peaceful when praying, being afraid to sin, and being grateful to God, aspects of knowledge. by knowing the procedures for worship such as etiquette into the bathroom and neighbour's manners, behavioral aspects by doing things that Allah likes in accordance with religious rules and norms that apply in society such as maintaining cleanliness, helping, giving charity, saying sorry, being forgiving, maintaining friendship with loyal friends and togetherness. Based on the religious values contained in the animated film Nussa and Rara, it can be used as an alternative as a medium for learning literature in elementary schools to be applied in everyday life.